2023
DOI: 10.1021/acs.jpcc.3c01185
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of CO2 on Amorphous and Crystalline Zirconia: A DFT and Experimental Study

Abstract: Herein, we study the structural and electronic origins of molecular adsorption using experiments and density functional theory (DFT) calculations. We performed X-ray diffraction (XRD) and temperature-programmed desorption (TPD) of CO2 on amorphous zirconia (am-ZrO2) and crystalline (tetragonal and monoclinic) zirconia. Using molecular dynamics simulations, the bulk structures of am-ZrO2 and am-zirconium(IV) hydroxide (am-Zr(OH)4) were obtained and the reproducibility of the experimental structure was confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…This discrepancy can be explained by the differences in the CO 2 adsorption ability. Previously, we examined the relationship between the crystal structure of ZrO 2 and the CO 2 adsorption ability through experimental and computational chemistry . Our findings revealed that CO 2 molecules are strongly adsorbed, or easily activated, on m-ZrO 2 compared to amorphous ZrO 2 .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This discrepancy can be explained by the differences in the CO 2 adsorption ability. Previously, we examined the relationship between the crystal structure of ZrO 2 and the CO 2 adsorption ability through experimental and computational chemistry . Our findings revealed that CO 2 molecules are strongly adsorbed, or easily activated, on m-ZrO 2 compared to amorphous ZrO 2 .…”
Section: Resultsmentioning
confidence: 88%
“…In this study, we evaluated the performance of the catalysts using crystallized ZrO 2 as a support. Through combined experimental and computational approaches, it is shown that CO 2 molecules are more strongly adsorbed on crystalline ZrO 2 than on am-ZrO 2 ; in other words, crystalline ZrO 2 may efficiently activate CO 2 molecules. Herein, several types of Ru/m-ZrO 2 (m-: monoclinic) were prepared via incipient wetness impregnation and selective deposition methods, and the influence of the preparation methods on CO 2 methanation over Ru/m-ZrO 2 was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…First, we measured the specific surface area (SSA) and total pore volume by N 2 adsorption (Table 1). The SSA of ZnZr46, InZr09, and InZr22 is lower than that of amorphous ZrO 2 (approximately 200 m 2 g −1 ), 35 which is the raw material. This result was attributed to sintering at 500 °C during catalyst preparation.…”
Section: Resultsmentioning
confidence: 92%
“…The Zr atoms on the surface are classified into two types, and the replaced Zr atom acts as a strong Lewis site with longer Zr–O bonds. 34,35 Fig. S1 (ESI†) shows the positions of In and one oxygen vacancy (V O ).…”
Section: Methodsmentioning
confidence: 99%
“…First-principles (ab initio) methods within the framework of DFT are successfully used in modern materials science regarding condensed matter physics [39][40][41][42][43][44][45][46][47][48].…”
Section: Modeling Detailsmentioning
confidence: 99%